2016
DOI: 10.1111/1440-1681.12671
|View full text |Cite
|
Sign up to set email alerts
|

Troxerutin attenuates diet‐induced oxidative stress, impairment of mitochondrial biogenesis and respiratory chain complexes in mice heart

Abstract: Summary Mitochondrial abnormality is thought to play a key role in cardiac disease originating from the metabolic syndrome (MS). We evaluated the effect of troxerutin (TX), a semi‐synthetic derivative of the natural bioflavanoid rutin, on the respiratory chain complex activity, oxidative stress, mitochondrial biogenesis and dynamics in heart of high fat, high fructose diet (HFFD) ‐induced mouse model of MS. Adult male Mus musculus mice of body weight 25‐30 g were fed either control diet or HFFD for 60 days. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…As shown by our study, TRX treatment (100 mg/kg) reverses the 5-FU-induced increase of MDA levels and prevents GSH consumption in mice. The antioxidant effect of TRX shown in the present study has also been reported by several published studies in different experimental models [17][18][19]21,[57][58][59][60][61].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…As shown by our study, TRX treatment (100 mg/kg) reverses the 5-FU-induced increase of MDA levels and prevents GSH consumption in mice. The antioxidant effect of TRX shown in the present study has also been reported by several published studies in different experimental models [17][18][19]21,[57][58][59][60][61].…”
Section: Discussionsupporting
confidence: 90%
“…The body weight of mice was assessed daily prior to administration of the administered treatment to confirm the experimental model of 5-FU induced intestinal mucositis. The TRX doses considered in the current study are in accordance with those in previous published studies [19][20][21][22]61]. daily prior to administration of the administered treatment to confirm the experimental model of 5-FU induced intestinal mucositis.…”
Section: Experimental Protocol Of 5-fu-induced Intestinal Mucositissupporting
confidence: 69%
See 2 more Smart Citations
“…In addition to the above, Hbq1a encodes hemoglobin, theta 1A, which is closely connected with oxygen and iron binding, and impact the activity of oxygen transporter. It may be associated with anti-oxidative effects of TX[ 83 ]. GM5526 is mainly responsible for skeletal muscle tissue development and muscle filament sliding.…”
Section: Discussionmentioning
confidence: 99%